Sugar Treatments Can Induce AcLEAFY COTYLEDON1 Expression and Trigger the Accumulation of Storage Products during Prothallus Development of Adiantum capillus-veneris - Fang, Yu-Han; Li, Xia; Bai, Shu-Nong; Rao, Guang-Yuan (Frontiers in Plant Science, 2017)
A seed is an intricate structure. Of the two development processes involved in seed formation, seed maturation or seed program includes accumulation of storage products, acquisition of desiccation tolerance, and induction of dormancy. Little is known about how these processes were originated and integrated into the life cycle of seed plants. While previous investigation on seed origin was almost exclusively through fossil comparison in paleobotany, a wealth of information about the key role of LEAFY COTYLEDON1 (LEC1) in seed formation of spermatophyte inspired a new approach to investigating the seed origin mystery. Here we examined the expression pattern of AcLEC1 during the entire life cycle of Adiantum capillus-veneris, a non-seed plant, confirmed no AcLEC1 gene expression detectable in prothalli, demonstrated inductive expressed by both sucrose and glucose in prothalli. As expected, we found that sugar treatments delayed prothallus development, promoted differentiation of reproductive organs, and triggered accumulation of storage products. These findings demonstrated links between the sugar treatments and the induction of AcLEC1 expression, as well as the sugar treatments and the events such as accumulation of storage products, which is similar to those considered as seed maturation process in seed plants. These links support a modified hypothesis that inductive expression of LEC1 homologs during embryogenesis might be a key innovation for the origin of the seed program.